2017
DOI: 10.1371/journal.pone.0169831
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota in Infants Fed a Formula Supplemented with Bovine Milk Fat Globule Membranes - A Randomized Controlled Trial

Abstract: BackgroundIn a recent study, supplementation of infant formula with milk fat globule membranes (MFGM) decreased the incidence of otitis media in infants <6 months of age.ObjectivesThe aim of the present study was to characterize the oral microbiota in infants fed MFGM-supplemented formula and compare it to that of infants fed standard formula or breast milk.MethodsIn a prospective double-blinded randomized controlled trial, exclusively formula-fed infants <2 months of age were randomized to be fed experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
2
48
0
2
Order By: Relevance
“…Firstly, our results from the literature review show that delivery mode might be associated with a higher carriage of oral fungi in young age (Figure 2) and, on the other hand, in the light of our results, the type of diet of the infant (formula-fed or breast-fed infants) does not seem to have impact on oral yeast carriage, although it is currently recognized that fungi are present in human breastmilk [57]. These results may be explained by the antimicrobial factors of the human milk influencing the oral ecology [58], although further studies are necessary.…”
Section: Discussionsupporting
confidence: 60%
“…Firstly, our results from the literature review show that delivery mode might be associated with a higher carriage of oral fungi in young age (Figure 2) and, on the other hand, in the light of our results, the type of diet of the infant (formula-fed or breast-fed infants) does not seem to have impact on oral yeast carriage, although it is currently recognized that fungi are present in human breastmilk [57]. These results may be explained by the antimicrobial factors of the human milk influencing the oral ecology [58], although further studies are necessary.…”
Section: Discussionsupporting
confidence: 60%
“…While factors including prematurity, maternal intrapartum antibiotics, delivery mode and formula feeding all affect infant oral microbiota composition[ 30 32 ], the microbes from the maternal mouth as well as the mammary areola and breast milk are the primary sources of bacteria for the infant mouth[ 5 , 22 ]. In our study population, we detected a shared core of eight bacterial genera between breast milk and infant oral mucosa microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that MFGM supplementation of human infants (6–11 months of age) could reduce diarrhea episodes 15 or acute otitis media infections 16 , which might be related to oral microbiome changes 17 . MFGM have also shown to reduce differences in cognitive development 18 and serum lipid status 19 between formula- and breast-fed infants (from < 2 until 6 months of age) when supplemented in fed-formula.…”
Section: Discussionmentioning
confidence: 99%